Peran Aparatur Pemerintahan dalam Pelaksanaan Pembangunan Perdesaan Partisipatif di Kabupaten Bone dan Kabupaten Jeneponto Provinsi Sulawesi Selatan - Mappamiring Mappamiring; Ma’mun Sarma; Darwis S Gani; Pang S Asngari (Jurnal Penyuluhan, 2010)
The arrangement of government institutions in the region, especially in the rural level is very important and urgent. The dominant factors affecting participatory rural development in Bone and Jeneponto Regencies of South Sulawesi province are the aspect of leadership, quality of human resources, awareness and sensitivity, and the level of education of the officers and public awareness. Changing the culture and access to knowledge and technology, both among the officers and the society is the key to the success of participatory rural development. There are three important aspects in the effort to create the prospect of government management and participatory rural development aspects of leadership, good governance and the aspects of sensitivity and concern for the officers. The level of stakeholders participation in all elements Bone and Jeneponto regencies of South Sulawesi Province can be categorized as medium. Achievement motivation and increased competence to the officer should be a prerequisite condition of adequate welfare, a clear career path, and the improvement of internal aspects of the system and working procedures and institutional structures of government. Community empowerment program has been running really well, but there are still weak in terms of socialization, values and traditions of feudalism, bureaucracy, as well as from the aspect of consciousness of citizens. Another phenomenon in terms of community empowerment programs is that the public is more interested in the economically productive program, so that the training programs are often considered less important and less desirable. The most prominent problems of the community empowerment program are transparancy, supervision, and socialization, and community authorities targeted purely as sub optimal.Keywords: institutional governance, participatory, autonomy and government official